Preliminary analysis of the interacting pentad bands (ν2+2ν4, ν2+ν3, 4ν2, ν1+2ν2, 2ν1) of CF4 in the 1600 – 1800 cm−1 region. (March 2019) - Mattoussi, M.; Rey, M.; Rotger, M.; Nikitin, A.V.; Chizhmakova, I.; Thomas, X.; Aroui, H.; Tashkun, S.; Tyuterev, Vl.G.
Highlights: First line position and line intensity analysis for CF4 in the range 1600–1800 cm − 1 . Combination of ab initio predictions and high order contact transformations. Present analysis will be used for future HITRAN updates. Abstract: The Fourier transform spectrum of CF4 in the 1600–1800 cm − 1 was recorded in Reims by using a White-type multi-pass cell to provide a path length of 8.262 m. In the present work, all spectrum analyses and fits were realized using the MIRS software based on tetrahedral tensorial formalism. By combining non-empirical contact transformation Hamiltonians for line positions and ab initio ro-vibrational normal-mode predictions for line intensities, we are able to achieve a simultaneous fit of effective Hamiltonian and dipole moment parameters of several cold and hot bands of CF4 . Hamiltonian operator was expanded up to the sixth order for the ground state and for the { ν 2 + 2 ν 4, ν 2 + ν 3, 4 ν 2, ν 1 + 2 ν 2, 2 ν 1 } pentad. 1831 line positions were fitted to RMS of 1.5X10 −3 cm −1 . The standard deviation for line intensities for the cold bands { ν 2 + 2 ν 4, ν 2 + ν 3, 4 ν 2, ν 1 + 2 ν 2, 2 ν 1 } is of 1.1% and of 8% and 5% for the hot band transitions { 2 ν 2 + 2 ν 4 − ν 2, 2 ν 2 + ν 3 − ν 2 } and { ν 2 + 3 ν 4 − ν 4, ν 2 + ν 3 + ν 4 − ν 4 }, respectively. Graphic abstract: Image, graphical abstract